Hubungan Self Care Dengan Kejadian Penyakit Scabies Di Sekolah Usaha Perikanan Menengah (SUPM) Negeri Kota Agung Kabupaten Tanggamus Tahun 2020 - Reni Tri Subekti; Arena Lestari; Fitriyana Fitriyana (LPPM STIKes Panca Bhakti Bandar Lampung, 2021)
Scabies is a disease caused by ectoparasites lodged in human skin. The infection of scabies is instantaneously influenced by certain factors, including self-care. Self-care is an individual treatment for maintaining their health and it is influenced by values and abilities. The studies conducted by Ratnasari (2014) in Jakarta, Fauziah (2014) in Bandung, and Raharnie (2014) in Makasar explained that men tend to have a higher prevelance at 57,4%. One of the ideal environment for scabies transmission is a dormitory environment, including the 1st Grade Student of SUPM Negeri Kota Agung’s dormitory. The purpose of this research was to determine the relationship between Self-care and scabies infevtions in SUPM Negeri Kota Agung Tanggamus Regency in 2020. The respondents of research were 89 who first grade students of SUPM Negeri Kota Agung. This research used the quantitative descriptive method withthe cross sectional approach. The applied statistic test was chi-square with 0,04<0,05 score of p-value and the results of univariate analysis showed that 62% of respondents had experienced symptoms of Scabies in low Self-care, 55,9% of respondents had experienced symptoms of Scabies in medium Self-care, and 13,3% of respondents had experienced symptoms of Scabies in high Self-care. The results also showed that there was a significant relationship between Self-care and scabies infections in 1st Grade Students of SUPM Negeri Kota Agung.